Two new species of nematodes from shallow and deep-water sediments in the South China Sea - Huang, Mian; Shi, Benze; Wang, Chunguang; Xu, Kuidong (Zootaxa, 2021)
Two new species of free-living marine nematodes from the South China Sea are described: Gomphionema setiforme sp. nov. from intertidal sediment and Paracomesoma longissimum sp. nov. from upper continental slope sediment. Gomphionema setiforme sp. nov. is characterized by the punctated cuticle without lateral differentiation and cuticular pores; short cephalic setiform sensilla; spiral amphideal fovea with 4 turns close to the anterior body extremity; large cuticularized buccal cavity with a massive dorsal tooth; pharynx with a large posterior bulb; short, curved spicules; knife-like gubernaculum without apophyses and 11 cup-shaped precloacal supplements. Paracomesoma longissimum sp. nov. is characterized by cuticle with transverse rows of fine punctuations without lateral differentiation; buccal cavity with three teeth; lateral outer labial setiform sensilla 1.5 times as long as the other four outer labial setiform sensilla; spiral amphideal fovea with 2.5 turns; spicules 350–360 μm long or 15.7–16 times cloacal body diameter; plate-like gubernaculum without apophyses and 25–28 papilliform precloacal supplements.